2007
DOI: 10.1136/gut.2007.119859
|View full text |Cite
|
Sign up to set email alerts
|

Risk for hepatocellular carcinoma with respect to hepatitis B virus genotypes B/C, specific mutations of enhancer II/core promoter/precore regions and HBV DNA levels

Abstract: CP-MT, T1653, HBV DNA levels >or=4 log(10) copies/ml and cirrhosis are independent factors for development of HCC. The risks increased substantially in patients having these factors in combination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(165 citation statements)
references
References 34 publications
6
157
2
Order By: Relevance
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, the current case-control study is the first to reveal the association between HBV mutations and the development of HCC among Thai patients. In this study, we found that double A1762T/G1764A mutations were an independent risk factor for the development of HCC, which was consistent with recent casecontrol studies conducted in China, Taiwan, and Korea [7,12,20,21]. Also, the magnitude of the OR of HCC associated with the presence of the BCP double mutants in this study was approximately 3 to 4-fold, which was similar with reports of other studies.…”
Section: Discussionsupporting
confidence: 92%
“…These dual mutants have been reported in up to 50-80% of patients with HBeAg-negative chronic hepatitis B in Europe and Asia [6], and have been implicated in HCC development [7][8][9]. Apart from these variants, other mutations, such as T1753C/A/G in the BCP region and C1653T in the enhancer II region (EnhII) have become increasingly recognized as being associated with the outcome of chronic HBV infection, including HCC development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies reported that genotype C was related to a higher risk of HCC development as compared to genotype B, although such association was not confirmed by other studies (Kim et al, 2011). Additionally, we found significantly higher frequencies of A1762T/G1764A and T1753A/G/C mutations in the HCC group than in controls, which are consistent with previous reports (Chen et al, 2008;Yuen et al, 2008). In fact, T1753A/G/C mutations are usually present along with the existence of A1762T/ G1764A mutations.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, Yuen et al from Hong Kong examined the risks for HCC with respect to HBV genotypes, specific viral mutants, serum HBV DNA levels, and cirrhosis in a case-control study, and multivariate analysis showed that core promoter mutant, T1653, HBV DNA ‡2,000 IU/ml, and cirrhosis were independent factors for HCC. In addition, the risks remarkably increased in HBV carriers with these factors in combination [90]. In Japan, an age-, sex-, and HBeAg status-matched cross-sectional control study was conducted to determine HCC-associated mutations of the HBV genome in the entire X, core promoter, and precore/core regions among 80 patients infected with HBV subgenotype C2 with HCC and 80 without HCC.…”
Section: Potential Interactions Between Known Hbv Factorsmentioning
confidence: 99%